Inhangapi Virus: Genome Sequencing of a Brazilian Ungrouped Rhabdovirus Isolated in the Amazon Region - Wanzeller, Ana Lucia M.; Nunes, Márcio R. T.; Tavares, Fernando N.; Pinto, Walber V. M.; Júnior, Edivaldo C.; de Lima, Clayton P. S.; de Oliveira, Layanna F.; Júnior, João Lídio S. G. V.; Cardoso, Jedson F.; Vasconcelos, Pedro F. C. (Genome announcements (Washington, DC), 2016)
We report here nearly complete genome sequence of Inhangapi virus (INHV) strain BEAR177325, which was isolated from a pool of sandflies ( Lutzomyia flaviscutellata ) in the Utinga neighborhood, Belém (01º28´S 48°27′W), State of Pará, Brazil, in 1969. The genome of this virus showed similarity with members belonging to the family Rhabdoviridae .